Oral proteases: a new approach to managing coeliac disease. Issue 2 (1st September 2006) - Cerf-Bensussan, Nadine; Matysiak-Budnik, Tamara; Cellier, Christophe; Heyman, Martine
Abstract : A life-long but constraining gluten-free diet is the only treatment currently available for coeliac disease. The human gastrointestinal tract does not possess the enzymatic equipment to efficiently cleave the gluten-derived proline-rich peptides driving the abnormal immune intestinal response in patients with coeliac disease. Oral therapy by exogenous prolylendopeptidases able to digest ingested gluten was therefore propounded as an alternative treatment to the diet. The feasibility of this approach is discussed by reviewing recent data on the intestinal transport of gliadin peptides, properties of available enzymes and preliminary clinical assays. Development of new enzymes or enzymatic cocktails offers potentially more potent therapeutic tools that, however, need meticulous evaluation based on clinical, biological and histological criteria.